Pernikahan anak usia dini ditinjau dari perspektif perlindungan anak - Fransiska Novita Eleanora; Andang Sari (PROGRESIF: Jurnal Hukum, 2020)
Children marriage of children at a very early marriage performed under adult age which is prohibited by law or other rules and regulations because it can cause things that can harm women. The impact that occurs from marriage a serious problem that must be with appropriately and seriously by the parties as well as the relevant agencies. Because the results in future generations caused by first high number of children who experience unwanted pregnancy and childbirth. Second, this also results in divorce. Third, the birth of a baby who later does not grow properly. Fourth, children are victims of divorce have the potential to fall into poverty, fail in education, get trapped trafficking children, are placed in degrading work such as sex workers, drug dealers, slavery. These are all in violation of child rights. The method in research in using normative juridical research is by principles and theories reviewing books, documents, journals, as well as from invitation legislation relating to the problem to be studied. The result is the prevention of child marriage at a very young age is the protection of children's rights, especially the protection of the right to life, the right to grow and must remain protected.